Speculative incentives to hoard aluminum: Relationship between capital gains and inventories. (March 2021) - Kim, Soohyeon; Kim, Jihyo; Heo, Eunnyeong
Abstract: This study explores the relationship between the capital gains and inventory in the aluminum market. We provide analytical evidence concerning how the increase in opportunities for speculative incentives from aluminum inventories caused an unprecedented purchase of inventories between 2009 and 2014. In this study, adjusted basis represents monetary and non-monetary value gained from holding inventory; if positive, this shows capital gains occurring from inventory, and if negative, the absolute value of the adjusted basis represents the convenience yield. Unlike the previous literature on convenience yields which assumes uniform relationship between adjusted basis and inventory throughout the period, we open the possibility of time-variance between variables by using dynamic linear model (DLM) and the time-varying parameter-vector autoregression-stochastic volatility (TVP-VAR-SV). A series of analysis in this study suggests clear evidence of inventory having been increased in pursuit of the monetary profit opportunities in the aluminum market. Highlights: Evidences of relationship between capital gains and inventories in the aluminum market. Time-varying analysis with DLM and TVP-VAR-SV on adjusted basis and inventory. Aluminum inventory increases in pursuit of monetary profit opportunities.